Call centres and job satisfaction in Italy: employment conditions and socio-biographical patterns. Issue 1 (2nd January 2020) - Arcidiacono, Davide; Avola, Maurizio; Palidda, Rita
ABSTRACT: The article examines job satisfaction in 21 Italian call centres. The results of research carried out on 1715 handlers indicate how dissatisfaction prevails among call centre representatives (CCRs) and how it is influenced by aspects related to some organisational characteristics (service delivered, size and organisational typology), on one side, and to different aspects of working conditions (contract, wage and tenure) and participants' biographical and working profiles of CCRs (gender, age, educational attainment), on the others. However, the most interesting finding emerges by distinguishing different dimensions of job satisfaction (extrinsic and intrinsic-relational). In particular, the relationship between type of contract and job satisfaction is rather interesting. For non-permanent workers, in fact, the probability of being dissatisfied is decidedly greater if we consider the extrinsic dimension of job satisfaction. Instead, when the intrinsic-relational dimension is taking into account, atypical workers are no more dissatisfied than the permanent ones. Job insecurity and limited perspectives in terms of work alternatives, safeguards and rewards, seem to be the source of greatest dissatisfaction for Italian CCRs. This certainly does not surprise considering the Italian development model and its dualistic labour market, highly segmented between insiders and outsiders.